2014
DOI: 10.1111/acer.12463
|View full text |Cite
|
Sign up to set email alerts
|

Acute Binge Alcohol Administration Reverses Sleep-Wake Cycle in Sprague Dawley Rats

Abstract: Background Binge alcohol drinking is amongst the most common pattern of alcohol consumption in our society. Binge alcohol consumption has serious negative consequence on mental and physical health. Although alcohol consumption is known to have profound impact on sleep, it is yet unknown as to how binge alcohol affects/alters sleep-wakefulness. The objective of this study was to examine the effect of acute binge alcohol administration on sleep-wakefulness. Methods Male Sprague-Dawley rats were used in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…There was a dose-response relationship between sleep problems and frequency of binge drinking, consistent with our study. In addition, Sharma et al 59 found that binge drinking could reverse sleep-wake cycle in rats and produce symptoms of insomnia, which could provide some explanation for the association between insomnia and binge drinking among students in the current study.…”
Section: Discussionsupporting
confidence: 54%
“…There was a dose-response relationship between sleep problems and frequency of binge drinking, consistent with our study. In addition, Sharma et al 59 found that binge drinking could reverse sleep-wake cycle in rats and produce symptoms of insomnia, which could provide some explanation for the association between insomnia and binge drinking among students in the current study.…”
Section: Discussionsupporting
confidence: 54%
“…Since BF and AD are key substrates involved in sleep homeostasis, we suggest that AD and BF may be critical in mediating alcohol-induced sleep. It is entirely possible that, along with AD and BF, alcohol may concurrently (directly or indirectly) inhibit multiple wake-promoting systems [for an example, see Sharma, Sahota, & Thakkar, 2014c] while activating sleep-promoting systems. More research is necessary to understand how and where alcohol acts to promote sleep and cause sleep disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this is the first step toward understanding the mechanism of sleep disruptions induced by binge drinking. Still, many questions remained unanswered such as a) how long do the effects of acute binge drinking on sleep homeostasis last, b) if sleep homeostasis is affected, does it play any role in reducing sleep-promoting effects of subsequent alcohol consumption which we have observed in our recent study (Sharma et al, 2014b), and c) what is the molecular mechanism responsible for altered sleep homeostasis?…”
Section: Sleep Homeostasis In Binge Alcohol-induced Sleep Disruptionsmentioning
confidence: 95%
See 1 more Smart Citation
“…The percent time spent in each state was grouped into two 3 h bins and used for further analysis. Sleep onset latency [amount of time in minutes between alcohol administration and first non-interrupted 60 s bout of NREM sleep; see (Thakkar et al 2010b)], bout frequency, and average duration of each bout (for all three states) were also determined (Sharma et al 2014b). Spectral analysis was also performed to examine NREM delta power (1-4 Hz).…”
Section: Sleep/wake Recording and Analysismentioning
confidence: 99%